How do you solve (p -> q) <=> (p /\ `q -> c)?
How do you solve (p -> q) <=> (p /\ `q -> c)?
To solve this logical equivalence, we need to show that the left-hand side of the equation is logically equivalent to the right-hand side of the equation.
Here are the steps to show that (p -> q) <=> (p /\ `q -> c) is a valid logical equivalence:
- Start with the left-hand side of the equation: (p -> q).
- Use the definition of the implication operator to rewrite this as
p v q
, wherev
represents the logical OR operator. - Now consider the right-hand side of the equation: (p /\ `q -> c).
- Use the definition of the implication operator to rewrite this as
~(p /\ ~q) v c
, where~
represents the logical NOT operator. - Use De Morgan’s law to rewrite
~(p /\ ~q)
as~p v q
. - Substitute this into the previous equation to get
(~p v q) v c
. - Use the associative law to rearrange the parentheses and get
~p v (q v c)
. - Use the definition of the implication operator to rewrite this as
p -> (q v c)
. - Now we have shown that the left-hand side, (p -> q), is logically equivalent to the right-hand side, (p /\
q -> c), which we rewrote as
p -> (q v c)`.
Therefore, we have shown that (p -> q) <=> (p /\ `q -> c) is a valid logical equivalence.